PROXIMATE COMPOSITION, SENSORY EVALUATION AND PRODUCTION OF COOKIES (BISCUIT) FROM FINGER MILLET AND WHEAT FLOUR - Bashir, Musa; Ibrahim, Aminu; Idi, Aminu; Abdulmalik, Muhammed (FUDMA JOURNAL OF SCIENCES, 2022)
Finger millet (Eleusinecoracana), is an important staple food because of its excellent storage properties, and nutritive value, resistance to disease and tolerance to soil moisture stress. The aim of this study is to determine the nutritional composition of cookies (Biscuit) produced from combination of finger millet and wheat flour and its sensory properties. Biscuit was produced from the formulated ratios (W:F 100, FM:100, W:F 95:5, W:F 90:10 and W:F 80:20) of wheat and finger millet respectively. Proximate composition and sensory evaluation were carried out using standard methods. The results of proximate composition for ration W:F 95:5 shows significant different compare to other ratios and individual flours, additionally the same product shows highly acceptable by the respondent for its taste, flavor and texture than cookies of other composition. Therefore it can be concluded that the product from formulated ratio WF: FM 95%:5% was best cookies highly acceptable. However consumption of such products are highly encouraged and less course effective.